2005
DOI: 10.1088/0957-0233/16/8/001
|View full text |Cite
|
Sign up to set email alerts
|

A study of an electronic nose for detection of lung cancer based on a virtual SAW gas sensors array and imaging recognition method

Abstract: In this paper, we propose an electronic nose for non-invasive detection and diagnosis of lung cancer based on a kind of virtual array of surface acoustic wave (SAW) gas sensors and an imaging recognition method. It includes a gas path constructed from a two-bag system, solid phase micro extraction (SPME) and a capillary column to pre-concentrate and separate volatile organic compounds (VOCs) in patients' exhaled air. A pair of SAW sensors, one coated with a thin polyisobutylene (PIB) film, is used to detect ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 16 publications
1
79
0
Order By: Relevance
“…163,164 (6) Finally, several groups have undertaken efforts to detect lung cancer. [165][166][167][168][169][170] To conclude, the possibilities for the application of the electronic nose in the medical field are very diverse as the different examples have shown. There is a need for preventive medical checkups to diagnose disease early, to speed up the healing process, to increase the rate of complete recovery, and consequently to save money for the health care system.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…163,164 (6) Finally, several groups have undertaken efforts to detect lung cancer. [165][166][167][168][169][170] To conclude, the possibilities for the application of the electronic nose in the medical field are very diverse as the different examples have shown. There is a need for preventive medical checkups to diagnose disease early, to speed up the healing process, to increase the rate of complete recovery, and consequently to save money for the health care system.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…To overcome the limitations of GC-MS analysis, various types of electronic nose have come into use for analyzing breath gas. In the previous studies, quartz microbalance (QMB) gas sensors [21], surface acoustic wave (SAW) gas sensors [22], colorimetric sensor array [23], polymer/carbon composite [24], conducting polymer gas sensors [25], ion mobility spectrometry [26], exhaled breath condensate (EBC) [27], and metal oxide gas sensors [28] were applied to lung cancer detection through breath gas. Among them, the metal oxide sensors are known to possess several advantages with high sensitivity, very fast response, and low cost [29].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, various previous studies have reported about its application in common environmental gases detection, including theoretical and experimental studies [19][20][21][22], while, until now, there is no study on Ni-SWCNTs sensors used to detect lung cancer by breath gases. In this study, we propose a novel way to detect typical breath gases of lung cancer: benzene (C 6 H 6 ), styrene (C 8 H 8 ), isoprene (C 5 H 8 ), and 1-hexene (C 6 H 12 ) by theory computation [23,24]. The adsorption reactions for C 6 H 6 , C 8 H 8 , C 5 H 8 , and C 6 H 12 gases on carbon nanotubes are calculated based on density functional theory (DFT); the sensitivity of carbon nanotubes for these gases was analyzed.…”
Section: Introductionmentioning
confidence: 99%